2020
DOI: 10.1002/dev.22045
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone regulates the emission of ultrasonic vocalizations and mounting behavior during different developmental periods in mice

Abstract: Testosterone masculinizes the brain and bodily functions and promotes the development of male characteristics. In the brain, there is a critical period during which testosterone acts on neural circuits to stimulate the development of male-type neural characteristics.Early exposure to testosterone masculinizes reproductive, cognitive, emotional, and neurophysiological functions, such as stress responses (McCarthy & Arnold, 2011). In the developing mammalian brain, testosterone can either be metabolized to estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Further analysis of testosterone and estrogen in the mouse brain after TP injections is needed to clarify this issue. In contrast, adult testosterone treatment has been shown to mimic testosterone secretion in intact males [17]. These perinatal and adult treatments induced USVs and mounting behavior in females at a similar level to that seen in intact males, indicating that testosterone was sufficient to induce male sexual behavior, as previously reported [8,17].…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Further analysis of testosterone and estrogen in the mouse brain after TP injections is needed to clarify this issue. In contrast, adult testosterone treatment has been shown to mimic testosterone secretion in intact males [17]. These perinatal and adult treatments induced USVs and mounting behavior in females at a similar level to that seen in intact males, indicating that testosterone was sufficient to induce male sexual behavior, as previously reported [8,17].…”
Section: Discussionsupporting
confidence: 54%
“…The neural mechanisms underlying the emission of USVs with complex call types, different frequency calls, and the pattern of transition of call types are yet to be uncovered. We previously reported that the neural circuits underscoring USV emissions and mounting behavior differ; the emission of USVs depends on the main olfactory circuit [2,17]. Mice lacking the dorsal region of the main olfactory bulb demonstrated a decrease in USV emissions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations